Just a Click Away: The Role of Available Mobile Technologies at NU Library - Baidyussenova, Gulzhan; Manabat, April (Nazarbayev University Library, 2020)
Purpose of the study. Libraries have a decent chance to broaden innovative library services to users. With the assistance of emerging mobile technologies, libraries can now provide speedier access to services with just a click away. Given the convenience provided by these mobile technologies, it is indeed material for libraries to not just explore the benefits of these technological innovations, but also to educate people how to maximize their use. The Nazarbayev University Library (NUL) has been exploring these technologies for quite some time now. As such this study aims to provide a review of the distinctive mobile technologies available at the NU Library. It also intends to identify the benefits of these technologies as perceived by students during the Library Road Show-2018. Moreover, the study seeks to determine possible ways to promote these mobile technologies to patrons to maximize its use. Methodology. A random survey was conducted among the participants during the “Library Road Show 2018” held at the atrium of the Nazarbayev University last 2018. The event showcased the different technologies available in the library. Ten questions were asked to random participants who visited the event and made use of the available mobile technologies available at the library such as Prestigio and Jet Book. The questions revolved around the use of these technologies and users’ perceptions about them. Based on these perceptions and other observations, the researchers were able to determine possible ways to promote these mobile technologies to maximize use. Findings. Based on the survey conducted, it was found out that not all participants knew how to make use of the available technologies available at NU Library. In addition, most of them were not aware that these mobile technologies were already available for use at the library. Moreover, the majority of the participants appreciated the value of these mobile technologies even without the knowledge that these mobile technologies are actually available at the library. Practical applications. This paper aims to describe the available mobile technologies at NU Library. Since an increasing number of services that help patrons in their research needs were provided by the library, this study will provide a glimpse of these technologies and its use. In addition, this study will help the library in coming up with possible ways to promote these technologies to the NU community. Conclusion. Libraries use several tools and techniques to disseminate information to their community. Marketing and promotion of these services to maximize its use is important. Based on the study, there were a number of mobile technologies available for use for the library patrons such as Overdrive and Prestigio among others. The use of technology as a tool in delivering services to patrons is essential to provide efficiency and convenience without sacrificing the quality of service. Promoting these technologies through exhibits and events like library roadshows, gamifications, and others will be a great help in increasing and maximizing its usage.
Keywords: mobile technologies; NU library; mobile applications